Malolactic fermentation in red wines: impact of the application of the cherry (P. avium) and oak (Q. pyrenaica and Q. petraea) wood chips on the phenolic characteristics of red wines - Randazzo, Gabriele (2022)
Mestrado em Engenharia de Viticultura e Enologia (Double degree) / Instituto Superior de Agronomia. Universidade de Lisboa / Faculdade de Ciências. Universidade do Porto